Analysis of satellite remote sensing and driver-pressure-state-impact-response framework in Selangor river basin area - Sayad Romli, Muhammad Syed Iqbal; Ibrahim, Illyani; Ahmad Sarkawi, Azila; Fadzil, Kamal Solhaimi; Tengku Hamzah, Tengku Adeline Adura; Abu Samah, Azizan (Prince of Songkla University, 2022)
Forest resources have come under growing pressure over time that led to forest degradation. The goal of this research is to use remote sensing to examine land cover changes in the study region, and then to construct the DPSIR framework for future decision making. Datasets of four Landsat images were based upon to produce the land-cover map and identify the land-cover changes. The Landsat images’ methodology of land-cover classification was unsupervised pixel-based classification. The specific land cover includes forest, built-up area, bare land, vegetation, water bodies, and cloud. Image classification found that forest changed between 1990 and 2020 were decreasing, respectively, at 17.05 percent of total change. An increase was noted in the built-up area, by 18.56 percent over the 30-year timeline. Factors contributing to the decrease of forest include anthropogenic factor. A DPSIR framework was produced to provide the relevant indicators and allow policymakers to contribute input on environmental concerns of the future impact in policy development.